The Regularities of the Regional Asymmetry of Small and Medium Enterprise Development - Bilchak, Vasiliy; Duplenko, Natalia (Olsztyn Economic Journal, 2013)
The aim of the conducted study was to identify the regularities of the regional asymmetry of development of small and medium enterprise. The subject of the study is the influence of the area factors on the activities of small and medium-sized businesses. The authors are proposing their own original method of assessment of the regional asymmetry of small and medium enterprise development. The study enabled the authors to identify the following regularities. Firstly, the level of the regional asymmetry of small and medium enterprise development does not depend on the size of the area occupied by the region. Secondly, the level of the asymmetry is inversely proportional to the level of the economic development of the region. Besides that, the case study ofthe North-West federal district ofthe Russian Federation revealed a number of features of the regional asymmetry of small and medium enterprise development in the countries having significant territorial expanse.